A new species of Tremella s.s. (Tremellaceae, Basidiomycota) from southeastern China - Fan, Long Fei; Pu, Jin Bao; Wu, Fang; Dai, Yu Cheng (Phytotaxa, 2021)
A new species Tremella zhejiangensis is described from southeastern China based on phenotypic and molecular evidence. The species is characterized by soft gelatinous, yellowish brown to brownish orange, cerebriform basidioma when fresh, thin-walled, globose to subglobose or broadly ellipsoid basidia with a basal clamp connection, globose to subglobose basidiospores measuring 15.0–19.0 × 14.0–17.5 µm with obvious apiculus, and growth on rotten wood of Liquidambar formosana. The phylogeny of Tremella s.s. is constructed using methods of Maximum Parsimony, Maximum Likelihood and Bayesian Inference analyses based on the combined internal transcribed spacer regions (ITS) and the large subunit (nLSU) dataset. The results indicate that T. zhejiangensis forms a lineage independent of other species of Tremella s.s. An illustrated description of the new species is provided and related species are discussed.